Analisis Pemasaran Cabai Rawit di Kecamatan Lawa Kabupaten Muna Barat - Saputri, Endeng; Limi, Muhammad Aswar; Yusria, Wa Ode (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to determine the marketing channels for cayenne pepper in Lawa District, Muna Barat Regency, to determine the profit costs and marketing margins for each marketing channel in Lawa Distric, Muna Barat Regency. And to analyze the efficiency of each marketing channel for cayenne pepper in Lawa Distric, Muna Barat Regency. Determination of the population using censustechniques (saturated sampling). Data analysis method using the Snowball Sampling method. The results of this study show 3 marketing channels for cayenne pepper in Lawa Distric. channel I has a farmer’s Share value of 90%, in marketing channel II has a Farmer’s Share of 72% and on marketing channel III has a Farmer’s Share value od 75%. The high start of Farmer’s Share on channel I is caused by the short marketing channel that producers go trough in marketing cayenne pepper .